2022
DOI: 10.1186/s40479-022-00182-0
|View full text |Cite
|
Sign up to set email alerts
|

The ICD-11 classification of personality disorders: a European perspective on challenges and opportunities

Abstract: The 11th revision of the World Health Organization (WHO) International Classification of Diseases (ICD-11) includes a fundamentally new approach to Personality Disorders (PD). ICD-11 is expected to be implemented first in European countries before other WHO member states. The present paper provides an overview of this new ICD-11 model including PD severity classification, trait domain specifiers, and the additional borderline pattern specifier. We discuss the perceived challenges and opportunities of using the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 54 publications
1
52
0
5
Order By: Relevance
“…These findings suggest another possible mechanism to explain why vulnerable narcissists are at risk of PSNSU. Because of their low frustration tolerance [ 45 ], people with vulnerable narcissism may use SNSs to obtain immediate gratification [ 46 ]. In fact, SNSs may facilitate a gratification-seeking process (e.g., through controlling self-presentation [ 47 ]), as is the case in other forms of addictive behaviors (e.g., [ 48 ]).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest another possible mechanism to explain why vulnerable narcissists are at risk of PSNSU. Because of their low frustration tolerance [ 45 ], people with vulnerable narcissism may use SNSs to obtain immediate gratification [ 46 ]. In fact, SNSs may facilitate a gratification-seeking process (e.g., through controlling self-presentation [ 47 ]), as is the case in other forms of addictive behaviors (e.g., [ 48 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The American Psychiatric Association has developed a diagnostic interview assessing personality functioning—the Structured Clinical Interview for the DSM-5 Alternative Model for Personality Disorders Module I (SCID-5-AMPD-I, [ 10 ]). An interview measure for the ICD-11 is currently still being constructed [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Czech version demonstrates that the results can be interpreted well both looking at the total score of personality dysfunction, as well as viewing the self and interpersonal dysfunction as separate facets of personality dysfunction [ 15 ]. Currently it is a well-accepted and recommended instrument in the good clinical practice of personality assessment that works for both the DSM5 as well as the ICD-11 classification systems [ 2 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies found mixed results regarding the incremental utility of traits and personality dysfunction (e.g., [19]). As the ICD-11 personality disorder model is currently entering global clinical practice [20][21][22], its links with relevant psychopathology domains are gaining increasing attention (e.g., [18,23,24]). Yet, to date, no study has investigated associations of the ICD-11 personality disorder model with eating pathology.…”
Section: The Icd-11 Personality Disorder Modelmentioning
confidence: 99%